소비자의 라이프스타일과 인터넷 쇼핑몰에서의 상품별 구매횟수 관계 연구 - 김시월; Kim Si Wol; 박배진; Park Bae Jin; 박혜령; Park Hye Lyeong (한국의류산업학회지, 2004)
The purpose of this study was to understand the relationship between life style that a consumer is pursuing and purchasing frequency among the purchasing behaviors in internet shopping mall. As a result, the factors of life style with respect to purchasing attitude of the consumer were categorized into `price advising type`, `price-quality identifying recognition type`, `brand-oriented type`, `shopping time-effort non-investment type`, and `price-quality comparing type`. It showed that there was a close relationship between the life style and the purchasing frequency in internet shopping mall and that there was a significant influence between the life style and the purchasing frequency. The result of this study indicated that the relationship between the life style and purchasing frequency in internet shopping mall was actualized by measuring the purchasing inclination of the consumer under various situations of psychologically descriptive characteristics and desire and simulation. Therefore, this fact suggests that it is very important to measure the accurate pur-chasing attitude of its consumer when setting up the marketing strategy of internet shopping mall.